The relationship between anxiety and serum Urotensin-II and S100B levels in patients with essential hypertension - Kazgan, Asli; Korkmaz, Sevda; Yildiz, Sevler; Korkmaz, Hasan; Telo, Selda; Atmaca, Murad (Klinik Psikiyatri Dergisi, 2021)
Objective: In hypertensive people, some biochemical parameters that are associated with oxidative stress and endothelial functions may play a role in the manifestation of anxiety symptoms, and even in the intensification of clinical symptoms of the disease. The purpose of our correlative study is to examine the association between anxiety severity and levels of oxidative stress parameters of Urotensin-II and S100B protein in patients with essential hypertension. Method: A total of 153 patients, who have applied Sociodemographic and Clinical Data Form, Beck Anxiety Inventory (BAI), Beck Depression Inventory and venous blood samples were taken after blood pressure measurement. S100B and Urotensin-II levels were measured with Enzyme-Linked Immunosorbent Assay method. Results: A positive correlation was determined between depression and anxiety scores, and systolic blood pressure (p=0.049, r=0.160; p<0.01, r=0.292). There was a positive relation between BAI scores and Urotensin-II levels (p= 0.043, r=0.164). A positive correlation was determined between Urotensin-II levels and S100B levels (p<0.01, r=0.711). A statistically significant difference was observed in serum Urotensin-II levels between depression group and no depression group (p=0.017). Discussion: It was determined in our study that Urotensin-II level increased with increasing anxiety level in essential hypertension patients. It was also determined that Urotensin-II level was higher in hypertensive patients with depression compared to patients who don't have depression. Our study will shed light on new studies that will investigate the contribution of Urotensin-II and S100B in the etiology of patients diagnosed with essential hypertension, which is very commonly accompanied by anxiety and depressive symptoms.
Esansiyel hipertansiyonlu hastalarda anksiyete ile serum ürotensin-II ve S100B seviyeleri arasındaki ilişki
Keywords: Essential hypertension; anxiety; urotensin-II; S100B